Exudаtive pericarditis: eight years of clinical experience. Part I: data from clinical trials and statistical studies - Telepov, V. V.; Salo, S. V.; Trembovetskaya, E. M.; Rudenko, E. V.; Ganul, V. L.; Borisyuk, B. O.; Starosyla, D. B.; Sokoliuk, M. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The aim of this review is to analyze and to discuss the methods of exudative pericarditis (EP) research including also new ones, being important for the understanding of this problem on the territory of Ukraine. For this purpose, we have chosen the most “popular” EP types; they were investigated in our country during 29 years, i.e. during 21 years before the introduction of new technologies and 8 years following this event; we describe here comparative qualitative and quantitative characteristics of different EP types.